Paying attention to the Construct Of Salience In Identity-related Literature and Beyond - Anderson, H.; Matheny, J. (AUT Faculty of Business, 2004)
This paper reviews the salience construct, proposing a definition of salience as a phenomenon of connection between a stimulus and a person. Our framing of the salience construct includes its elements, temporality, and several ontological perspectives of salience. In answer to calls for clarity in the use of concepts in the identity-related literature, this framing is applied to Identity Theory and Social Identity Theory. We find each theory unclear in its use of salience, the naming of the elements of salience and the ontological perspective of salience. The importance of gaining clarity in defining and using salience is the contribution to answering questions inherent to identity theories, namely ‘Is an identity triggered by an object of salience, or does the active identity determine which objects of salience gain attention?’ Research propositions based on the proposed definition of salience and the results of the analysis are offered. The implications a precise definition of salience has for identity-related literature and micro-organisational theories, such as leadership and motivation, are briefly outlined.